1980
DOI: 10.1029/jc085ic09p05003
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic aperture radar imaging of ocean waves: Comparison with wave measurements

Abstract: Synthetic aperture radar images of ocean waves were obtained in conjunction with reference wave data near Marineland, Florida, December 14, 1975. Each of the various types of measurements were processed into a form that allowed direct comparisons with the others. Maxima of radar spectra occurred at the same frequencies as the maxima of reference wave height spectra. In a comparison of a radar spectrum with observed spectra of wave height, wave orbital velocity, and surface slope the high-frequency portion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Since that time, several authors have addressed SAR imagery of the ocean using both point target and distributed scatterer models [Jain, 1978;Swift and Wilson, 1979;Alpers and Rufenach, 1979;Valenzuela, 1980;Harger, 1980;Shuchman et al, 1981;Rufenach and Alpers, 1981;Raney, 1981;Jain, 1981;Alpers, 1982]. The results of these efforts have not always been consistent; attempts to check their predictions against experiment are still underway [Gonzalez et al, 1979;Beal, 1979;McLeish et al, 1980;Shuchman, 1981;Alpers et al, 1981;Beal et al, 1983]. One convenient instrument with which SAR imagery of the ocean could be compared is the two-scale radar wave probe [Wright et al, 1980].…”
Section: Introductionsupporting
confidence: 92%
“…Since that time, several authors have addressed SAR imagery of the ocean using both point target and distributed scatterer models [Jain, 1978;Swift and Wilson, 1979;Alpers and Rufenach, 1979;Valenzuela, 1980;Harger, 1980;Shuchman et al, 1981;Rufenach and Alpers, 1981;Raney, 1981;Jain, 1981;Alpers, 1982]. The results of these efforts have not always been consistent; attempts to check their predictions against experiment are still underway [Gonzalez et al, 1979;Beal, 1979;McLeish et al, 1980;Shuchman, 1981;Alpers et al, 1981;Beal et al, 1983]. One convenient instrument with which SAR imagery of the ocean could be compared is the two-scale radar wave probe [Wright et al, 1980].…”
Section: Introductionsupporting
confidence: 92%
“…Previous experiments with aircraft SAR's have shown that it is possible to detect the dominant wavelength and direction of a surface wave field [Shemdin et al, 1978;Gonzalez et al, 1979;McLeish et al, 1980;Pawka et al, 1980]. The shape of in situ and SAR-derived surface wave spectra, however, show large differences.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging of gravity waves in the ocean by synthetic aperture radar (SAR) has been amply demonstrated by several investigators • Gonzalez et al, 1979;McLeish et al, 1980;Shuchman et al, 1983], although there is still disagreement as to the exact mechanisms responsible for this imaging. In particular, the relative importance of hydr0dynamic modulation,, tilt modulation, and velocity bunching is no.t well known [Alpers et al, 1981;Harger, 1981;Jain, 1981].…”
Section: Introductionmentioning
confidence: 99%